Dose‐Dependent Carbon‐Dot‐Induced ROS Promote Uveal Melanoma Cell Tumorigenicity via Activation of mTOR Signaling and Glutamine Metabolism. Issue 8 (25th February 2021) - Ding, Yi; Yu, Jie; Chen, Xingyu; Wang, Shaoyun; Tu, Zhaoxu; Shen, Guangxia; Wang, Huixue; Jia, Renbing; Ge, Shengfang; Ruan, Jing; Leong, Kam W.; Fan, Xianqun
Abstract: Uveal melanoma (UM) is the most common intraocular malignant tumor in adults and has a low survival rate following metastasis; it is derived from melanocytes susceptible to reactive oxygen species (ROS). Carbon dot (Cdot) nanoparticles are a promising tool in cancer detection and therapy due to their unique photophysical properties, low cytotoxicity, and efficient ROS productivity. However, the effects of Cdots on tumor metabolism and growth are not well characterized. Here, the effects of Cdots on UM cell metabolomics, growth, invasiveness, and tumorigenicity are investigated in vitro and in vivo zebrafish and nude mouse xenograft model. Cdots dose‐dependently increase ROS levels in UM cells. At Cdots concentrations below 100 µg mL −1, Cdot‐induced ROS promote UM cell growth, invasiveness, and tumorigenicity; at 200 µg mL −1, UM cells undergo apoptosis. The addition of antioxidants reverses the protumorigenic effects of Cdots. Cdots at 25–100 µg mL −1 activate Akt/mammalian target of rapamycin (mTOR) signaling and enhance glutamine metabolism, generating a cascade that promotes UM cell growth. These results demonstrate that moderate, subapoptotic doses of Cdots can promote UM cell tumorigenicity. This study lays the foundation for the rational application of ROS‐producing nanoparticles in tumor imaging and therapy. Abstract : Uveal melanoma (UM) originates from melanocytes that are susceptible to malignant transformation by reactive oxygen species (ROS). Carbon dots (Cdots) with efficient ROS productivity dose‐dependently promote UM cell growth, invasiveness, and tumorigenicity at concentrations below 100 µg mL −1 . Cdot‐induced ROS act as stimulatory signaling molecules to activate Akt/mammalian target of rapamycin signaling, accelerate glutamine metabolism, thus promoting UM cell growth.